Teori dan Model Perencanaan Pendidikan dalam Pengembangan Pendidikan Islam - Ziddan Arrauf; Nur Fahmuddin Hanif; Romlah Romlah; Abdurrahman Abdurrahman (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to analyze the theories and models of educational planning in the development of Islamic education through a literature review approach, focusing on how Islamic values can be integrated into educational management systems in the era of globalization and digitalization. This research employed a systematic literature review method by examining national and international scholarly sources published within the last five years that discuss theoretical, empirical, and policy aspects of Islamic educational planning. The findings indicate that Islamic educational planning is grounded in the principles of tawhid (oneness of God), amanah (trust), adl (justice), and maslahah (public interest) as moral and spiritual foundations in determining educational policies. Contemporary planning models, such as the rational-interactive model and the humanistic-Islamic planning model, strive to integrate modern managerial rationality with Islamic ethical values, enabling educational institutions to adapt to global changes without losing their Islamic identity. However, governance challenges—including limited infrastructure, human resource quality, resistance to innovation, and the tension between Islamic values and universal ethical standards—remain major obstacles. Therefore, a reconstruction of Islamic educational planning models that are ethically grounded, based on the principles of maqāṣid al-syarī‘ah, and responsive to technological and professional demands is essential for Islamic education to function as a moral and transformative force at the global level.